1990
DOI: 10.1021/bi00473a016
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of photoinhibition in hydroxylamine-extracted photosystem II membranes: relevance to photoactivation and sites of electron donation

Abstract: Kinetic analyses were made of the effects of weak-light photoinhibition on the capacity of NH2OH-extracted photosystem II membranes to photooxidize the exogenous electron donors Mn2+, diphenylcarbazide, and I- or to assemble functional water-oxidizing complexes during photoactivation. The loss of capacity for photooxidation of the donors showed two first-order components (half-times of 2-3 min and 1-4 h) with relative amplitudes dependent on the donor, suggesting two photodamageable sites of electron donation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
116
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 55 publications
14
116
0
1
Order By: Relevance
“…Thompson and Brudvig (50) assumed that specific antenna Chl not essential for the electron transfer are destroyed first. However, light saturation measurements yielded no evidence for a destruction of antenna Chl in PSII from Chlamydomonas (this work) or in grana membranes from higher plants (7,12,51). On the other hand, Telfer et al (23) proposed that the destruction of P680 is the cause of photoinhibition in PSII-RC.…”
Section: Discussionmentioning
confidence: 56%
“…Thompson and Brudvig (50) assumed that specific antenna Chl not essential for the electron transfer are destroyed first. However, light saturation measurements yielded no evidence for a destruction of antenna Chl in PSII from Chlamydomonas (this work) or in grana membranes from higher plants (7,12,51). On the other hand, Telfer et al (23) proposed that the destruction of P680 is the cause of photoinhibition in PSII-RC.…”
Section: Discussionmentioning
confidence: 56%
“…Experiments on PSII preparations and on leaves with chemically inactivated OECs indicate that the very high sensitivity of PSII to light appears to be caused by the impaired electron donation from the OEC. This, in turn, results in strong accumulation of highly oxidizing radicals, P680 + , Tyr Z + , and superoxide (Chen et al, 1995) or hydroxyl radicals (Spetea et al, 1997), and leads to a rapid inactivation and degradation of PSII reaction centers (Callahan et al, 1986;Blubaugh and Cheniae, 1990;Jegerschöld and Styring, 1996). This type of photodamage is called weak light or donor-side-induced photoinhibition.…”
mentioning
confidence: 99%
“…For example, susceptibility of PS II to photoinduced inactivation and protein degradation has been shown in hydroxylamine-treated leaf segments (Callahan et al, 1986), in leaves subjected to cold stress (Wang et al, 1992a), in Tris- (Wang et al, 1992b) and hydroxylamine-treated thylakoids (Blubaugh et al, 1990(Blubaugh et al, , 1991, and in thylakoids (Critchley et al, 1984;Jegerschöld et al, 1990). Eckert et al (1991) showed that the quantum yield of electron transport inactivation increases 1000-fold inTris-washed PS II enriched membranes inhibited reaction centers per quantum) as compared to normal oxygen evolving PS II membranes inhibited reaction centers per quantum).…”
Section: B Donor Side-induced Photodamagementioning
confidence: 99%
“…This is because the LF-1 mutant does not have water splitting activity due to its inability to process the carboxy-terminus of the D1 protein (Bowyer et al, 1992), while the absence of the 33 kDa extrinsic protein of PS II in the psbO-less Synechocystis mutant perturbs its donor side activity (Vass et al, 1992a). It is generally agreed that the site of donor side inactivation is between the manganese cluster and P680 (Eckert et al, 1991;Jegerschöld et al, 1990;Blubaugh and Cheniae 1990;Blubaugh et al, 1991). coworkers (1990,1991) resolved three kinetically different phases of inactivation in hydroxylamine treated PS II membranes.…”
Section: B Donor Side-induced Photodamagementioning
confidence: 99%